Socio-Economic Aspects of Accessibility to Museums and Galleries in Europe by Removing Barriers - ŠEBOVÁ, Ľubica; LAZUROVÁ, Izabela; MARČEKOVÁ, Radka (Theoretical and Practical Research in Economic Fields; Vol 15 No 2 (2024): TPREF, Volume XV, Issue 2(30), Summer 2024, Special Issue, 2024)
The paper deals with the theoretical and empirical investigation of socio-economic aspects of accessibility to museums and galleries by removing various barriers. While there are certain costs associated with barrier removal, making museum and galleries accessible also leads to an increase in visitor numbers, resulting in higher incomes. Thus, accessibility in turn, impacts both economy and society. The aim is to examine and identify the socio-economic aspects associated with making museums and galleries accessible to all and to compare the approach to this process in Slovakia and abroad. The study analyses primary data collected through a combination of questionnaire survey and interviews. The research sample consists of Slovak museums and galleries (n=52) and associations from 6 European countries. Results reveal that the main problem lies in the elimination of architectural barriers, which is caused by the historical nature of buildings and the financial difficulty associated with technical modifications. The lack of financial resources is as well considered to be a fundamental hindrance to the process of removing barriers. However, making culture accessible to people with disabilities is not driven by internal motivation, but rather by an obligation arising from the law. The findings also underscore that representatives from museums, galleries, and associations acknowledge that while the immediate economic benefits may not be readily apparent, the long-term impact on the institution's attractiveness and visitor experience and happiness is profound. Moreover, implemented modifications are beneficial to a significantly broader audience, which expands the potential target group and may contribute to employment.